Prevalence and distribution of Borrelia burgdorferi sensu lato genotypes among ixodid ticks in three regions of Ukraine - Panteleienko, O. V.; Garcia, D.; Bilyk, S. A.; Dovhal, O. V.; Tsarenko, T. M. (Regulatory Mechanisms in Biosystems, 2023)
To improve our understanding and to develop strategies to control Lyme borreliosis, this study focused on assessing the prevalence of clinically relevant Borrelia genotypes in ixodid ticks collected from different regions of Ukraine. Ixodid ticks were collected from vegetation and animal hosts in Kyiv, Cherkasy, and Mykolaiv regions of Ukraine (2021). The ticks were then tested by polymerase chain reaction (PCR) for the presence of the B. burgdorferi sensu lato complex and genotyped using primers for B. burgdorferi sensu stricto, B. afzelii, and B. garinii. In total, 1132 ixodid ticks were examined. In Kyiv region, Ixodes ricinus was the most common species (79.7%), in Cherkasy region, Dermacentor reticulatus was most common (72.7%), and in Mykolaiv region, Hyalomma marginatum was the most common species (76.4%). PCR analysis showed that I. ricinus and D. reticulatus are the main vectors of the B. burgdorferi sensu lato complex, especially in Kyiv and Cherkasy regions, where I. ricinus had a significantly higher total Borrelia infection rate (29.2%) than D. reticulatus (15.9%). In Mykolaiv region, Borrelia was not detected. Genotypic analysis revealed a significantly higher prevalence of the B. afzelii (15.6%) over the B. burgdorferi sensu stricto genotype at 9.3%. The B. garinii genotype was not detected in this study.This study analyzes the prevalence of ixodid ticks and genotypes of the Lyme borreliosis pathogen in Northern, Central and Southern Ukraine. In general, the results of the study indicate a widespread presence of borrelia in the northern and central regions, while no Borrelia were detected in the southern region. In addition, the B. afzelii genotype prevailed in Kyiv and Cherkasy regions.